Odpowiedzi

2009-11-25T14:20:11+01:00
-5x+x-2x=-12-12
-6x=-24/:-6
x=4

-2x-6+8x+12=-6
-2x +8x=-6+6-12
6x=-12/:6
x=-2

x- 7-2x=2x-2+1
x-2x-2x=-2+1+7
-3x=6/:-3
x=-2
Najlepsza Odpowiedź!
2009-11-25T14:21:29+01:00
A)-5x+12+x=2x-12
b)-2(x+3)+4(2x+3)=-6
c)x-(7+2x)=2(x-1)+1

a)-5x+12+x=2x-12=-5x+x-2x=-12-12
4x=-24 x=-6

b)-2(x+3)+4(2x+3)=-6=-2x-6+8x+12=-6
-2x-6+8x+12=-6 -2x+8x=-6-12+6
6x=-12
x=-2

c)x-(7+2x)=2(x-1)+1=x-7+2x=2x-2+1
x-7+2x=2x-2+1 x+2x-2x=-2+1+7
x=6
2009-11-25T14:23:03+01:00
-5x+12+x=2x-12
-5x+x-2x=-12-12
-6x=-24 /(-6)
x=4


-2(x+3)+4(2x+3)=-6
-6x-6+8x+12=-6
-6x+8x=-6+6-12
2x=-12/ 2
x=-6


x-(7+2x)=2(x-1)+1
x-7-2x=2x-2+1
x-2x-2x=-2+1+7
-3x=6/(-3)
x=-2